2010
DOI: 10.1371/journal.pone.0013586
|View full text |Cite
|
Sign up to set email alerts
|

Germline Met Mutations in Mice Reveal Mutation- and Background-Associated Differences in Tumor Profiles

Abstract: BackgroundThe receptor tyrosine kinase Met is involved in the progression and metastasis of numerous human cancers. Although overexpression and autocrine activation of the Met signaling pathway are commonly found in human cancers, mutational activation of Met has been observed in small cell and non-small cell lung cancers, lung adenocarcinomas, renal carcinomas, and mesotheliomas.Methodology/Principal FindingsTo investigate the influence of mutationally activated Met in tumorigenesis, we utilized a novel mouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Even though the knock-in mutation models never developed renal carcinomas, when placed on an FVB/N background, each Met mutant (except for D1226N) developed aggressive mammary carcinomas (11). Again, unique mammary carcinoma phenotypes were observed between the M1248T, Y1228C, and M1248T/L1193V lines (12). Since the only differences between these animals were the Met mutations and the murine background strain, this study indicated that either the mutated kinase structure itself or the level of kinase they impose (or both) influence the tissue-specificity for tumor formation.…”
Section: Met Kinase Domain Mutations In Hereditary Papillary Renal Camentioning
confidence: 96%
“…Even though the knock-in mutation models never developed renal carcinomas, when placed on an FVB/N background, each Met mutant (except for D1226N) developed aggressive mammary carcinomas (11). Again, unique mammary carcinoma phenotypes were observed between the M1248T, Y1228C, and M1248T/L1193V lines (12). Since the only differences between these animals were the Met mutations and the murine background strain, this study indicated that either the mutated kinase structure itself or the level of kinase they impose (or both) influence the tissue-specificity for tumor formation.…”
Section: Met Kinase Domain Mutations In Hereditary Papillary Renal Camentioning
confidence: 96%
“…Interestingly, preclinical studies in germline met mutations in a murine transgenic model reveal mutation- and background-associated differences in tumor profiles. 90 The most frequently detected MET mutation, N375S, occurred in 13% of East Asians compared to only 2.6% in whites and none among African Americans. MET mutations were also more likely to exist in male smokers and squamous cell carcinoma.…”
Section: Lung Cancer: Genes and Genomementioning
confidence: 97%
“…and colleagues (6) demonstrated that even a modest increase in MET activation can initiate tumorigenesis and that both the MET mutational spectra and the host stromal tissue background can have profound influence on the type of tumor generated. Hence, personalized combinational MET-targeting therapies would have to take into accounts of any interaction of genetic modifiers and MET oncogenic signaling.…”
Section: In the Spotlightmentioning
confidence: 99%